Adherence to Secondary Prophylaxis for Acute Rheumatic Fever an d Rheumatic Heart Disease: A Systematic Review - M. Kevat, Priya; M. Reeves, Benjamin; R. Ruben, Alan; Gunnarsson, Ronny (Current Cardiology Reviews, 2017)
Background: Optimal delivery of regular benzathine penicillin G (BPG) injections prescribed as secondary prophylaxis for acute rheumatic fever (ARF) and rheumatic heart disease (RHD) is vital to preventing disease morbidity and cardiac sequelae in affected pediatric and young adult populations. However, poor uptake of secondary prophylaxis remains a significant challenge to ARF/RHD control programs. Objective: In order to facilitate better understanding of this challenge and thereby identify means to improve service delivery, this systematic literature review explored rates of adherence and factors associated with adherence to secondary prophylaxis for ARF and RHD worldwide. Methods: MEDLINE was searched for relevant primary studies published in the English language from 1994-2014, and a search of reference lists of eligible articles was performed. The methodological quality of included studies was evaluated using a modified assessment tool. Results: Twenty studies were included in the review. There was a range of adherence to varying regimens of secondary prophylaxis reported globally, and a number of patient demographic, clinical, socio-cultural and health care service delivery factors associated with adherence to secondary prophylaxis were identified. Conclusion: Insights into factors associated with lower and higher adherence to secondary prophylaxis may be utilized to facilitate improved delivery of secondary prophylaxis for ARF and RHD. Strategies may include ensuring an effective active recall system, providing holistic care, involving community health workers and delivering ARF/RHD health education.
Keywords: benzathine benzylpenicillin